การใช้ระบบการรับรองแบบมีส่วนร่วมสู่เกษตรอินทรีย์ยุค 3.0 และเพิ่มรายได้ของเกษตรกรรายย่อย - มณีโชติ สวรรค์; อธินุวัฒน์ ดุสิต (Thai Journal of Science and Technology, 2019)
Abstract Application of participatory guarantee system (PGS) to organic farming movement within the small grower community was studied based on shared vision, trust - “integrity based approach”, horizontality, transparency, participatory, and learning process. National standard of Organic Thailand used organic products guarantee followed by PGS process and Organic 3.0 approach. Results showed that 34 growers passed organic farming certification system by PGS. Before PGS applied to small grower community, the average cost of organic farming was 1,512 bath per rai per year. After PGS applied, the average cost of organic farming was reduced to 450 baths per rai per year. This indicated that PGS reduced the cost production up to 70.23 %. Moreover, organic products price certified by PGS was increased 15-79 %. Its average revenue per rai per year was increased to 11.11 %. Furthermore, PGS enhanced woman farmer empowerment, improved human rights and health, helped people to reach quality organic foods, increased consumer acceptance, increased the strength of the group, and increased market channels. The farmers presented the most satisfaction with the certification of organic agriculture by the PGS system. Keywords: PGS; Organic farming folk way; guarantee by the community